Association of Overcrowding and Turnover with Self-Harm in a Swiss Pre-Trial Prison - Baggio, Stéphanie (Int J Environ Res Public Health, 2018)
Self-harm is a common issue in detention and includes both suicidal and non-suicidal behaviours. Beyond well-known individual risk factors, institutional factors such as overcrowding (i.e., when the prison population exceeds its capacity) and turnover (i.e., the rate at which the prison population is renewed), may also increase the risk of self-harm. However, these factors are understudied or previous studies reported inconsistent findings. This study investigated the association of self-harm with overcrowding and turnover in the largest pre-trial Swiss prison in Geneva. Data were collected yearly between 2011 and 2017. Measures included self-harm (all kinds of self-injuring acts requiring medical attention, including self-strangulations and self-hangings). We performed meta-regressions to analyse the relationships between self-harm and institutional factors. Self-harm events were frequent, with a prevalence estimate of 26.4%. Overcrowding and turnover were high (average occupation rate of 177% and average turnover of 73%, respectively). Overcrowding and turnover were significantly associated with self-harm (respectively b = 0.068, p < 0.001 and (b = 1.257, p < 0.001). In both cases, self-harm was higher when overcrowding and turnover increased. Overcrowding and turnover raise important human rights concerns and have damaging effects on the health of people living in detention. Identification of and care for this vulnerable population at risk of self-harm are needed and institutional factors should be addressed.